Headspace solid-phase microextraction analysis of the volatile flavour compounds of roasted chickpea (Cicer arienum L). - Olusegun, Lasekan; Juhari, Nurul Hanisah; Pattiram, Parveen Devi (OMICS Publishing, 2011)
Headspace-solid phase microextraction coupled with gas chromatography-mass spectrometry analysis were used to provide the volatile profile of roasted chickpea as a means of unravelling and elucidating roasted chickpea as a prerequisite in developing chickpea snack item for the health and functional food sectors. The results of the HSSPME and optimization analysis using response surface methodology showed that DVB/CAR/PDMS was the most effective fibre and further results revealed the extraction temperature to be the dominant factor. A total of 61 volatile compounds were identified in the roasted chickpea. The best response within the range studied was established at 60oC extraction temperature, 30 min of equilibrium time and 15 min of extraction time. The volatile compounds identified comprised of aldehydes (25%), hydrocarbons (25%), terpenoids (20%), esters (8%), ketones (8%), alcohols (8%) and heterocyclic (8%). The results further indicated that the final model was significantly (P < 0.05) fitted for the response variable (total flavour peak area) studied with a relatively high R 2(0.9658).